17. FACTORS RELATED TO SELF-CARE OF PEOPLE WITH TYPE 2 DIABETES AT HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Research objective: Analysis of some factors related to self-care of people with type 2 diabetes.Subjects and methods: Cross-sectional descriptive study on 362 patients with type 2 diabetes at Hanoi Medical University Hospital in 2023.Results: The study showed that 55.5% of subjects General self-care is good and 44.5% is not good. Among them: 93.6% of people take good care of themselves with a good medicine regimen, 72.7% of people take good care of themselves physically, 62.2% of people take good care of their feet, 27.1% of people know how to take care of their own nutrition, and 6.9% of people know how to check blood sugar well. Gender, education level and family history of diabetes are the main factors related to patient self-care with p < 0.05.Conclusion: Patients do not have good self-care behaviors, it is necessary to improve health education to improve knowledge to help patients perform better self-care to achieve the best treatment results and disease prevention and improve quality of life.
Keywords: Type 2 diabetes; self-care; SDSCA